Comparative Diagnostic Accuracy of Computed Tomography, Magnetic Resonance Imaging, and Ultrasonography for Acute Appendicitis: A Systematic Review - Arvin Diego Tandoyo; Hendwell (The International Journal of Medical Science and Health Research, 2025)
Introduction: The diagnosis of acute appendicitis (AA) remains a significant clinical challenge. While multiple imaging modalities are available, their comparative diagnostic accuracy is a subject of ongoing debate, particularly regarding the balance between diagnostic certainty and the risks associated with radiation or procedural limitations. Methods: This systematic review was conducted in accordance with the PRISMA-DTA (Preferred Reporting Items for a Systematic Review and Meta-analysis of Diagnostic Test Accuracy Studies) guidelines (Salameh et al., 2018). We performed a comprehensive search of PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library for diagnostic accuracy studies comparing Computed Tomography (CT), Magnetic Resonance Imaging (MRI), Ultrasonography (USG), and plain X-ray for acute appendicitis. A total of 18 primary studies were included. Methodological quality was assessed using the rigorous QUADAS-2 (Quality Assessment of Diagnostic Accuracy Studies-2) tool (Whiting et al., 2011). Pooled sensitivity, specificity, positive predictive values (PPV), and negative predictive values (NPV) were synthesized for each modality, utilizing a bivariate random-effects model where appropriate. Results: A clear three-tiered hierarchy of diagnostic accuracy was identified. Tier 1 (Superior) includes CT and MRI, which demonstrated statistically comparable and excellent accuracy. CT showed a pooled sensitivity of 97.2% and specificity of 95.6% (Kim et al., 2022). MRI showed a pooled sensitivity of 96.6% and specificity of 95.9% (Repplinger et al., 2016). Both modalities demonstrated exceptionally high negative predictive values (NPV) (> 98-99%) (Apisarnthanarak et al., 2015; Oto et al., 2009). Tier 2 (Situational) includes USG, which had lower and more heterogeneous accuracy (pooled sensitivity 81-87%, specificity 87-93%) (Anjum et al., 2024; Shen et al., 2023). The utility of USG was significantly limited by operator-dependence and a high non-diagnostic (indeterminate) scan rate, reported as high as 35.7% (SAGES, 2022). Tier 3 (Obsolete) includes plain X-ray, which was confirmed to have no diagnostic value in the modern workup of AA (Rao et al., 1998; Bhangu, 2020). Discussion: The diagnostic equivalence of CT and MRI (Moore et al., 2017) suggests the choice of modality should be based on patient factors rather than diagnostic performance alone. CT remains the most efficient modality for non-pregnant adults, aligning with 2024 IDSA guidelines (Bonomo et al., 2024). The "US-first" algorithm is validated as a radiation-mitigation strategy in pediatric and pregnant populations, but the high rate of inconclusive scans necessitates a reflex pathway to MRI, which serves as the definitive non-radiation test in these groups (Oh et al., 2016). Conclusion: CT and MRI are the most accurate imaging modalities for acute appendicitis. Ultrasonography serves as a critical, first-line triage tool in radiation-sensitive populations. Plain X-ray is obsolete for this indication. We recommend a stratified diagnostic algorithm, with the choice of modality tailored to the specific patient population (non-pregnant adult, pregnant, or pediatric) to optimize accuracy while minimizing harm.